Faktor prediktor social commerce intention - Rizky Laili Kurniasari; Burhanudin Burhanudin (Jurnal Manajemen Maranatha, 2022)
Social media is currently transforming from a medium of communication to a medium of communication and shopping. This role makes a greater understanding on social commerce intention important, however, research on social commerce intention within the Indonesian context is scarce.  This study examines the effect of guidance shopping affordance on trust in the seller and flow experience, and then on social commerce intention. The survey was then conducted to examine the proposed relationships. In recruiting the respondents, this study used a judgment sampling with the criteria of having a purchasing experience at TikTok Shop. A total of 249 respondents participated in the survey. This study used structural equation modeling to analyze the data. Consistent with the prediction, the results show guidance shopping affordance significantly affects trust in the seller and flow experience. Both trust in the seller and flow experience significantly affect social commerce intention.